Nephroprotective effect of turmeric on oxidative stress, renal histopathology and toxicity induced by gentamicin - Jogdand, Sangita Devrao; Shinde, Raju; Sinha, Vivek; Chandrakar, Naman (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Commonly used aminoglycosides have frequent side effect of nephrotoxicity, still are preferred by clinicians because of efficacy against gram negative bacteria, resistant bacteria, nosocomial infections and cost effectiveness. Gentamicin produces oxidative stress; substances ameliorating stress are used to reduce toxicity. Turmeric has multiple medicinal properties including potent antioxidant activity, hence study was undertaken. Methods: Eight groups containing six animals in each group, treated for 15 days. First group treated with normal saline. Second, fourth and sixth group treated with only gentamicin- sacrificed at 16, 22, 29th day. Third, fifth and seventh group treated with gentamicin and turmeric simultaneously and sacrificed on 16, 22, 29th day. Eighth group was pre-treated with turmeric for thirty days and concurrently treated with gentamicin and turmeric for 15 days and sacrificed on 16th day. Levels of blood urea, serum creatinine, superoxide dismutase and histopathological grades were assessed each time. Results: Severe renal dysfunction (146 ± 9.2, 2.03 ± 0.26), highest renal injury grading (3.66 ± 0.24) was observed in only gentamicin treated groups followed by spontaneous recovery after withdrawal of drug but with higher levels of oxidative stress (0.04 ± 0.01). Gentamicin and Turmeric treated groups maintained renal function and had lower level of renal damage grades and oxidative stress. Turmeric pre-treated group was having lowest oxidative stress (0.12 ± 0.03), histopathology grade (0.60 ± 0.06) with normal renal functions. Conclusions: Turmeric has potent antioxidant property which effectively protects kidney from damage induced because of gentamicin.